Analysis of Complex Time Function of Converter Output Quantities Using Complex Fourier Transform/Series - Maria Zaskalicka; Pavel Zaskalicky; Mariana Benova; Mahmud A. R. Abdalmula; Branislav Dobrucky (Communications - Scientific letters of the University of Zilina, 2010)
The paper deals with the complex- and discrete Fourier transform which has been considered for both three- and two phase orthogonal voltages and currents of systems. The investigated systems are power electronic converters supplying alternating current motors. Output voltages of them are strongly non-harmonic ones, so they must be pulse-modulated due to requested nearly sinusoidal currents with low total harmonic distortion. Modelling and simulation experiment results of half-bridge matrix converter for both steady- and transient states are given under substitution of the equivalence scheme of the electric motor by resistive-inductive load and back induced voltage. The results worked-out in the paper confirm a very good time-waveform of the phase current and results of analysis can be used for fair power design of the systems.